Heat transfer due to permeable stretching. Wall in presence of transverse magnetic field (Archives of Mechanics - Test, 2004)
Exact similarity solution for the viscous flow due to stretching surface in the presence of magnetic field is derived. Further exact solutions for the temperature distributions in terms of Kummer's functions are obtained. Two cases of heat transfer are considered: the sheet (i) with prescribed surface temperature and (ii) - the prescribed wall heat flux. Both the cases are further extended to study the heat transfer due to suction and injection. A simple relation for the two cases of heat transfer is obtained.